1993
DOI: 10.1111/j.1476-5381.1993.tb13616.x
|View full text |Cite
|
Sign up to set email alerts
|

Oestradiol inhibits smooth muscle cell proliferation of pig coronary artery

Abstract: 1 The effect of oestradiol 17p on vascular smooth muscle proliferation was examined in segments of the pig left anterior descending coronary artery (LAD). It was established by cytochemical techniques that out-growth from the segments was composed of vascular smooth muscle cells. 2 [3H]-thymidine uptake by pig LAD segments was used as an index of vascular smooth muscle cell proliferation. Nitroprusside and forskolin significantly inhibited [3H]-thymidine uptake and were used as positive controls. 3 Oestradiol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(65 citation statements)
references
References 28 publications
4
60
0
1
Order By: Relevance
“…It has been well demonstrated that 17b-estradiol exhibits hypertrophy of uterine smooth muscle 19 but inhibits smooth muscle cell proliferation in porcine coronary. 20 Fotsis et al reported that the endogenous estrogen metabolite 2-methoxyestradiol inhibits angiogenesis in vitro. 21 In castrated or estrogen-treated animals, Data are expressed as mean AE standard deviation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well demonstrated that 17b-estradiol exhibits hypertrophy of uterine smooth muscle 19 but inhibits smooth muscle cell proliferation in porcine coronary. 20 Fotsis et al reported that the endogenous estrogen metabolite 2-methoxyestradiol inhibits angiogenesis in vitro. 21 In castrated or estrogen-treated animals, Data are expressed as mean AE standard deviation.…”
Section: Discussionmentioning
confidence: 99%
“…Based on current models of atherosclerosis and restenosis after vascular injury (41,42), the known effects of estrogen, and the data presented here, a number of mechanisms might contribute to the estrogen effects on the response-to-injury observed in the present study. These potential mechanisms include (a) direct effects of estrogen on vascular smooth muscle cell proliferation (suggested previously in cell culture [23,24] and animal studies [9,[18][19][20][21][22] ); (b) inhibition of the synthesis and/or deposition of vascular matrix elements that contribute to lesion growth in injured vessels (43-45); (c) an altered rate of re-endothelialization after injury (17); and (d) estrogen inhibition of the inflammatory response in the injured vessel wall (46). This study was undertaken in C57BL/6J mice in part so that the mechanism of any effect noted might be studied next in C57BL/6J transgenic mice lacking the estrogen receptor (25,47).…”
Section: Discussionmentioning
confidence: 99%
“…In cultured vascular cells and tissue, 17,3-estradiol (E2)' also has been reported to inhibit the growth of vascular smooth muscle cells derived from rabbit aorta (23), and porcine coronary artery (24). However, interpretation of the effects of estrogen on atherogenesis and vascular cell growth in previous studies is complicated by the use of supraphysiologic (micromolar) estrogen dosing, atherogenic (high cholesterol) diets, and/or the absence of measured levels of circulating hormone.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, growth inhibition was observed in response to estrogen in vascular smooth muscle cells that normally express tuberin (33,(42)(43)(44). Thus, we examined the effect of tuberin expression on the growth of ELT-3 cells in response to estrogen.…”
Section: Tuberin Binds To Er␣ In Vivo and Modulates Growth Of Elt-3 Cmentioning
confidence: 99%